More "Daju-Bhai" and "Didi-Bahini," Less "Janajati" and "Adivasi": Re-reading the Debates of Ethnicity and Indigeneity in Nepal - Chalaune, Prem Bahadur (Nepal Journal of Sociology, 2024)
In this expository paper, I aim to illuminate the intricate political processes shaping the discourse of ethnicity and Indigeneity through a collaborative framework involving NEFIN (Nepal Federation of Indigenous Nationalities), International Organizations, Anthropologists, researchers, and the Nepali state. This study delves into the socio- political importation and imposition of the term “Indigenous people,” examining its origins, development, and transformation from ethnicity to indigeneity - a shift orchestrated by a select few and adopted by many. Through a detailed sociological lens, I trace the reemergence of this new construct, highlighting how it has been engineered and adopted across various spheres. By integrating my analysis with the critical perspectives of scholars who have engaged thoughtfully with these issues, I provide a nuanced picture of the situation both within Nepal and beyond. Finally, I argue that both the ideas of ethnicity and Indigenous as ambiguous and ambivalent in the Nepali context, suggesting that their continued use could potentially lead to further conflicts.